2015
DOI: 10.1080/00224545.2014.977762
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Situation Awareness: Validation of the Situationism Scale

Abstract: This paper concerns the construct of lay situationism—an individual’s belief in the importance of a behavior’s context. Study 1 identified a 13-item Situationism Scale, which demonstrated good reliability and validity. In particular, higher situationism was associated with greater situation-control (strategies to manipulate the environment in order to avoid temptation). Subsequent laboratory studies indicated that people higher on the situationism subscales used greater situation-control by sitting farther fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 50 publications
3
6
0
2
Order By: Relevance
“…The second type of behaviour, situation-control, refers to manipulating the environment in order to avoid temptation. Roberts et al (2015) found that individual differences in situationism and its subscales could predict greater situation-control. For instance, when individuals were asked not to snack from bowls of junk food, those self-regulators with higher scores on the Attention to the Situation subscale sat farther away from the food (with distancing oneself from tempting food being a type of situation-control strategy).…”
Section: The Situationism Scale and Self-regulationmentioning
confidence: 99%
See 4 more Smart Citations
“…The second type of behaviour, situation-control, refers to manipulating the environment in order to avoid temptation. Roberts et al (2015) found that individual differences in situationism and its subscales could predict greater situation-control. For instance, when individuals were asked not to snack from bowls of junk food, those self-regulators with higher scores on the Attention to the Situation subscale sat farther away from the food (with distancing oneself from tempting food being a type of situation-control strategy).…”
Section: The Situationism Scale and Self-regulationmentioning
confidence: 99%
“…The Situationism Scale (Roberts, Gibbons, Gerrard, & Klein, 2015) was developed to assess individual differences in beliefs about the strength of the relation between the environment and one's own behaviour. Scale validation with US samples supported the psychometric soundness of this Situationism Scale, and the distribution of scores supported the notion that situationism can vary within cultures.…”
Section: The Situationism Scale and Self-regulationmentioning
confidence: 99%
See 3 more Smart Citations